Lineage tracing of Sca1-expressing cells in the heart and skeletal muscle - De Gaspari, Piera; Justus Liebig University Giessen (My University, 2014)
Different types of resident adult stem cells exist in mammalian organs in order to maintain tissue homeostasis and organ repair. Even though the heart has low regenerative capacity it has been demonstrated that resident adult stem cells exist and are able to replace smooth muscle cells, endothelial cells and damaged or lost cardiomyocytes. Currently, the origin and the identity of cardiac resident adult stem cells remain controversial. In this study, descendants of cells that have expressed Sca1, which is one of the most widely used adult stem cell markers, were traced. Their contribution to self-renewal in the heart during aging and under pathological conditions was characterized. In both conditions, Sca1-expressing cells could differentiate into three major cardiac lineages, providing evidence of their role in myocardial renewal. These cells appeared to be a heterogeneous population in vivo as well as at a transcriptomic level, showing a specific location in the heart. Unlike the heart, skeletal muscle shows a high regenerative potential. It contains adult resident progenitor cells called satellite cells , which are able to differentiate into mature muscle fibers. Although satellite cells are considered to be the principal stem cells in the skeletal compartment, recent works have identified alternative sources of multipotent stem cells that are positive for Sca1. In this study, an in vivo lineage tracing approach in skeletal muscle revealed that Sca1-expressing cells are involved in skeletal muscle regeneration, although their contribution is lower compared to satellite cells. It was also possible to identify a small population of Sca1-expressing cells able to differentiate into muscle fibers without expressing Pax7, a marker for satellite cells known to be involved in quiescence, proliferation and differentiation of myogenic cells. Furthermore, the plasticity of satellite cells and Sca1-expressing cells was tested in vivo and was confirmed by gene expression profiling analysis. The data obtained verified that satellite cells are unipotent stem cells only able to regenerate skeletal muscle fibers. In contrast to satellite cells, Sca1-expressing cells are revealed to be multipotent and have the ability to differentiate into adipocytes and osteoblasts.In conclusion, this study confirmed the presence of Sca1-expressing cells that are able to contribute to myocyte regeneration in the heart and skeletal muscle. Further characterization of these Sca1-expressing cells will provide valuable insights into the molecular mechanisms regulating cardiac and muscle stem cells in humans. Importantly, this could aid the future development of therapeutic strategies for human cardiac and skeletal muscle diseases.

Zur Aufrechterhaltung der Homöostase und der Regeneration von Geweben und Organen existieren im Säugetierorganismus verschiedene residente adulten Stammzellen. Der Herzmuskel besitzt nur eine geringe Selbstheilungsfähigkeit, welche durch lokale adulte Stammzellen ermöglicht wird. Diese sind in der Lage, glatte Muskelzellen, Endothelzellen oder auch beschädigte Kardiomyozyten zu ersetzen. Die Herkunft und die Identität dieser kardialen adulten Stammzellen sind nicht eindeutig definiert. In diese Arbeit ein genetisches Zellmarkierungssystem verwendet, das gezielt Sca1-exprimierende Zellen markiert und damit eine in vivo Verfolgung der genetischen Abstammung dieser Zellen ermöglicht. Sca1 ist einer der am häufigsten verwendeten adulten Stammzellmarker. Die Analyse der markierten Zellen im Herzen ergab, dass sowohl im Alterungsprozess als auch unter pathologischen Bedingungen die von Sca1-abstämmenden Zellen zu den drei wesentlichen kardialen Zelllinien differenzieren. Dies deutet auf eine Rolle von Sca1-exprimierenden Zellen bei der kardialen Selbsterneuerung hin. Sowohl in vivo als auch Transkriptomdaten zeigten, dass diese eine heterologe Zellpopulation bilden und eine spezifische Lokalisation im Herzen besitzen. Die Skelettmuskulatur besitzt hingegen ein hohes regeneratives Potential. Ermöglicht wird dies durch adulte Vorläuferzellen, die Satellitenzellen, welche zu Skelettmuskelfasern differenzieren können. Obwohl Satellitenzellen als grundlegende Stammzellquelle im Skelettmuskel gelten, wurden in den letzten Jahren alternative Quellen von multipotenten Zellpopulationen, die Sca1 exprimieren, beschrieben. Mit Hilfe des in vivo Zellmarkierungsmodells konnten wir zeigen, dass Sca1-exprimierende Zellen an der Muskelregeneration, wenn auch in wesentlich geringerem Maße als Satellitenzellen, beteiligt sind. Darüber hinaus konnte nachgewiesen werden, dass eine kleine Population Sca1-exprimierender Zellen unabhängig von Pax7, in Muskelfasern differenzieren kann. Desweiteren wurde die Plastizität von Satellitezellen und Sca1- exprimierenden Zellen in vivo untersucht und durch Genexpressionanalysen bestätigt. Diese Daten belegten, dass Satellitenzellen eine unipotente Stammzellpopulation darstellen, die nur Muskelfasern regenerieren können. Dagegen zeigten sich Sca1-exprimierenden Zellen multipotent und waren in der Lage zu Adipozyten oder Osteoblasten zu differenzieren. Somit konnte ich darlegen, dass Sca1-exprimierende Zellen in der Lage sind, zu Regeneration von Myozyten beizutragen. Eine weitere Charakterisierung dieser Sca1-exprimierende Zellen wird wichtige Erkenntnisse über den molekularen Mechanismus, welcher Herz- und Muskelstammzellen im Menschen reguliert, liefern. Diese Erkenntnisse könnten hilfreich sein, um mögliche therapeutische Behandlungen für Herz- und Skelettmuskelerkrankungen zu entwickeln.
In vivo Verfolgung der genetischen Abstammung Sca1-exprimierender Zellen im Herzen und der Skelettmuskulatur
Keywords: ddc:570